Critiquing sovereign violence : law, biopolitics, and bio-juridicalism - Rae, Gavin, 1982- (Edinburgh scholarship online., 2019)
Gavin Rae offers an original approach to sovereign violence by looking at a wide range of thinkers, which he organises into three models. Benjamin, Schmitt, Arendt, Deleuze and Guattari form the radical-juridical perspective; Foucault and Agamben the biopolitical; Derrida the bio-juridical - which Rae argues produces the most nuanced account.